High-energy monitoring of NGC 4593 II. Broad-band spectral analysis: testing the two-corona model. Issue 4 (13th December 2018) - Middei, R; Bianchi, S; Petrucci, P-O; Ursini, F; Cappi, M; De Marco, B; De Rosa, A; Malzac, J; Marinucci, A; Matt, G; Ponti, G; Tortosa, A
ABSTRACT: It is widely believed that the primary X-ray emission of AGN is due to the Comptonization of optical-UV photons from a hot electron corona, while the origin of the 'soft-excess' is still uncertain and matter of debate. A second Comptonization component, called warm corona, was therefore proposed to account for the soft-excess, and found in agreement with the optical-UV to X-ray emission of a sample of Seyfert galaxies. In this context, we exploit the broad-band XMM–Newton and NuSTAR simultaneous observations of the Seyfert galaxy NGC 4593 to further test the so-called 'two corona model'. The NGC 4593 spectra are well reproduced by the model, from the optical/UV to the hard X-rays. Moreover, the data reveal a significant correlation between the hot and the warm corona parameters during our monitoring campaign.